(untitled) (Journal of Imam Al-Kadhim College, 2025)
Abstract This Study assesses the extent to which technological competencies have been adopted and mainstreamed in some of the ELT textbooks in Iraq in consonance with current educational needs. Analyzing the content of the First Intermediate Student Book and Activity Book, this research reveals that there are important Areas of omission and lack of direct integration of digital tools and online resources in the material. While the textbooks looked at here show a clear understanding of the four basic skills of language teaching which includes reading, writing, listening, and speaking skills, none is very specific on technology. Such practices as creating posters, scrapbooks, and listening comprehension could be supported by the use of additional application (for instance, Canva, PowerPoint, corresponding online platforms for sharing audio materials, etc.), as it was pointed out no suggestions in this regard were made. Furthermore, there is no information on how the teachers can guide their students to use the technology making the textbooks lacking in their abilities to inform students on the technological advancement. This can only call for an urgent relocation of ELT material to trends that can equip the students to face a technologically enhanced learning environment. The guidelines are the following: using technologies in their teaching, incorporating internet and AI technologies and tools for research purposes, encouraging project-based assignments using documents stored on Google Drive, and offering training to the teachers regarding the suggested tools. An awareness of these demands should be incorporated into the selection and design of ELT materials, arguing that improved technological support can help to develop both the foreign language and relevant digital competencies of Iraqi students.